Levantes urbanos: o ciclo de lutas pós crise do capitalismo de 2008 - Maíra Ramirez Nobre (2019)
After the 2008 crisis of capitalism important parts of the world were taken by a sequence of urban uprisings that had as main feature the occupation of social networks, streets and squares. Cities such as Tunis, Cairo, New York, Madrid and Sao Paulo were the scene of demonstrations by thousands of activists who championed the most diverse agendas. Composed of members of the very new social movements, these struggles were marked by the creation of a new form of organization that profoundly modified the bases of the more traditional and newer movements. The activists, different from the militants, have left aside a tree structure of organization and reinvented themselves according to a rhizomatic logic, that is, horizontal webs, self-managed, flexible, decentralized, adaptable networks that, according to themselves, spread like weeds. This "brand-new" way of rising by taking networks and streets is part of a process that has been happening in various parts of the world, especially since the 1980s, with the acceleration of globalization and exponential growth of neoliberalism. The rhizome characteristics are not unique to contemporary resistance organizations, but they are part of the neoliberal logic itself. Neoliberalism represents a world reason from which no subject or State is able to escape. That is, it also crosses the biopower of the multitude that it tries to resist. In view of this contradictory situation, it is necessary to have a deeper understanding of the complexity involved in these processes, which in this dissertation include: narratives, agendas, antagonisms, financing, actors and agencies. In order to be able to carry out this analysis, it is necessary to understand that there are two main spaces for the action of these uprisings that had the creation of an intense network of communication and affections: the city (mainly streets and squares) and the internet (mainly social networks), and thus, the development of a technopolitical research is fundamental for the construction of this investigation. It takes place mainly through the analysis of three uprisings that have been highlighted in this cycle of struggles since 2008: Spain's 15M, Occupy Wall Street in New York in 2011 and the 2013 June Journeys, in Brazil.